Home gardens and agrobiodiversity - Eyzaguirre, Pablo B.; Linares, O.F. (2004)
Smithsonian books has published Home Gardens and Agrobiodiversity, edited by Pablo Eyzaguirre and Olga Linares. What is a home garden? The editors write that ”home gardens are microenvironments within a larger farming system that contain high levels of species diversity and may contain crop species or varieties of species different from those found in surrounding agroecosystems.” They are thus important as reservoirs of agricultural biodiversity and the knowledge to make use of it. The book contains three sections. The first deals with Theory and Methods. It covers, for example, the importance of microenvironments for the selection, evolution and maintenance of home garden plants. The second is a survey of research results from a global project on home gardens, carried out by the International Plant Genetic Resources Institute and national partners in seven countries and funded by the German Agency for Technical Cooperation (GTZ). The third is in some measure a synthesis of the first two, and looks at how the genetic diversity of key crops can be managed and conserved in home gardens. ”Theres a great deal of diversity in home gardens,” said Eyzaguirre, ”but the most important thing is that everywhere weve looked, people keep the crops they really value close to home. Thats the way to look after agricultural biodiversity.” Eyzaguirre is a senior scientist at Bioversity International in Rome and Linares is a staff scientist at the Smithsonian Tropical Research Institute, Panama. Linares is also a member of Bioversity's Board of Trustees.